Nursing Care for Clients Gout Arthritis by Providing Cupping Therapy in Bawangan Hamlet, Pajarakan Kulon Village Probolinggo - Elvin Nur Avian, Moch.; Rahman, Handono Fatkhur; Heru, Maulidiyah Junnatul Azizah (Research of Service Administration Health and Sains Healthys, 2024)
Introduction: Gouty arthritis is a type of arthritis that occurs due to a buildup of uric acid crystals due to excessive levels in the blood and high levels of uric acid in the body can cause the joints to be attacked, especially the toes, knees, heels, wrists, fingers and elbows. Treatment for gouty arthritis can be done pharmacologically, namely with anti-pain medication and non-pharmacologically, such as cupping therapy. Objective: in this final scientific work, it is to determine the description of the provision of cupping therapy in nursing care for gout (Goat Artitis) patients. Method: This final scientific work uses the case study method. This method is carried out by observing clients with gouty arthritis who are given cupping therapy intervention and the instruments used use the SOP for giving cupping to reduce pain and reduce excessive purine levels. Results and discussion: Before the cupping therapy intervention was given, the patient complained of pain in the joints of both right and left knees. The patient looked restless, the patient's face appeared to be grimacing complaining of pain, BP: 130/80 mmHg, S: 36.5 C, N: 80 x / minutes, RR: 20x / minute, Uric Acid 8.9 mg/dL. After the intervention of providing cupping therapy, the patient appeared calmer, the patient appeared to improve, Uric Acid was 5.2 mg/dL. Conclusion: From the implementation results, it was found that the intervention of providing cupping therapy had an effect on reducing pain and reducing high purine levels.